Preparation, Characterization, and Evaluation of Cytotoxicity of Fast Dissolving Hydrogel Based Oral Thin Films Containing Pregabalin and Methylcobalamin - Emrah Özakar; Rukiye Sevinç-Özakar; Bilal Yılmaz (Gels, 2023)
The oral availability of many drugs is problematic due to the pH of the stomach, enzymes, and first-pass effects through the liver. However, especially geriatric, pediatric, bedridden, or mentally handicapped patients and those with dysphagia have difficulty swallowing or chewing solid dosage forms. Oral Thin Films (OTFs) are one of the new drug delivery systems that can solve these problems. Pregabalin (PG) and Methylcobalamin (MC), which are frequently preferred for pain originating in the central nervous system, were brought together for the first time using OTF technology in this study. In this study, a quantification method for PG and MC was developed and validated simultaneously. Optimum formulations were selected with organoleptic and morphological controls, moisture absorption capacity, swelling capacity, percent elongation, foldability, pH, weight variability, thickness, disintegration time, and transparency tests on OTFs prepared by the solvent pouring method. Content uniformity, dissolution rate, determination of release kinetics, SEM, XRD, FT-IR, DSC, long-term stability, and cytotoxicity studies on the tongue epithelial cell line (SCC-9) were performed on selected OTFs. As a result, OTFs containing PG-MC, which are non-toxic, highly flexible, transparent, compatible with intraoral pH, with fast disintegration time (<30 s), and acceptable in taste and appearance, have been developed successfully.